Effect of a Multispecialty Faculty Handoff Initiative on Safety Culture and Handoff Quality. Issue 2 (30th March 2022) - Fitzgerald, Katie M.; Banerjee, Taruna R.; Starmer, Amy J.; Caplan, Gregory H.; Alkuwari, Mohammed; Hillier, Debra F.; Stack, Anne M.
Abstract : Introduction: Structured handoffs at transitions of care are vital components of patient safety. A safety culture survey showed that "handoffs and transitions" were among the lowest scoring dimensions at our hospital. We sought to improve physician handoffs and safety culture scores by implementing standardized handoff communication across multiple divisions of an academic pediatric department. Methods: We used a modified learning collaborative model to implement an I-PASS program, including training, standardized verbal handoff processes, observation and feedback, and sustainment. The setting was the Department of Pediatrics (DoP) within a tertiary academic children's hospital encompassing 13 clinical divisions. The primary outcome was a change in the DoP staff physician "handoffs and transitions" score on the Agency for Healthcare Quality (AHRQ) Hospital Survey on Patient Safety Culture. Process measures included handoff duration and proportion of handoffs using the complete I-PASS mnemonic. Results: Five hundred sixty-seven physicians from clinical divisions participated over 14 months. One hundred percent of eligible physicians completed an introductory online I-PASS training module. The "handoffs and transitions" score improved from 46% to 54% from 2018 to 2020. From May 2019 to February 2020, the proportion of observed handoffs with all five elements of the I-PASS mnemonic improved from 62% to 100%, and the duration of handoffs per patient did not change. Conclusions: We successfully implemented an I-PASS program across an academic department of pediatrics. The departmental staff physician safety culture "handoff and transitions" score improved. The adherence to the I-PASS mnemonic improved. The duration of handoffs did not change over the study period.